Retirees’ motivation for wellness tourism activities: Thailand case study / Nanthawat Suetrong and Ann Suwaree Ashton - Suetrong, Nanthawat; Ashton, Ann Suwaree (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
Wellness tourism is one of the niche tourism market that are very important for all aged, especially for retirement group. Hence, the development of activities is to suit for this age group will be benefit for stakeholders at a destination related to wellness product and services. Interesting and right activity will add value and gave competitive advantage for retirement age group. Moreover, it helps to reduce health care if they have good health from attending an exercising in wellness activity. This study focuses on motivation of the retirement age group toward wellness activity. A qualitative approach was conduct using an in-depth interview technique for the data collecting process while content analysis technique was used to analyze data. Thirty-seven participants were interviewed during September 2020. A motivation theory was adapted for this study. The result revealed that attraction, safety, facilities, and service most affected the retirement age group to do more wellness tourism activities. This study provides knowledge for both theoretical and managerial contributions.